[Rezension von: F.S. Naiden, Soldier, priest, and god. A life of Alexander the Great] - Trampedach, Kai (De Gruyter, 2022)
F.S. Naiden, Soldier, priest, and god. A life of Alexander the Great], Oxford - New York (Oxford University Press) 2019, 424 S., ISBN 978-0-19-087534-3 (geb.), £ 20,99
In: Klio, 104 (2022), Nr. 1. pp. 379-383. ISSN 0075-6334 (Druck-Ausg.); 2192-7669 (Online-Ausg.)
Keywords: Rezension